2006
DOI: 10.1073/pnas.0601562103
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila glucosyltransferase inhibits host elongation factor 1A

Abstract: Legionella pneumophila, the causal agent of Legionnaires' disease, is an intracellular parasite and invades and proliferates within different eukaryotic cells, including human alveolar macrophages. After several 100-fold multiplication within host cells, the pathogens are released for new invasion by induction of apoptosis or necrosis. Here we report that L. pneumophila produces a glucosyltransferase, which selectively modifies an Ϸ50-kDa mammalian protein by using UDP-glucose as a cosubstrate. MS analysis ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(165 citation statements)
references
References 46 publications
4
155
1
2
Order By: Relevance
“…Addition of purified glucosyltransferase to S. cerevisiae translational extract inhibited protein synthesis in a dose-dependent manner. These results were similar to those obtained with mammalian reticulocyte lysates recently (12,13). Also similar to experiments with mammalian cells, expression of lgt1 in the cytosol of S. cerevisiae resulted in severe toxic effects.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Addition of purified glucosyltransferase to S. cerevisiae translational extract inhibited protein synthesis in a dose-dependent manner. These results were similar to those obtained with mammalian reticulocyte lysates recently (12,13). Also similar to experiments with mammalian cells, expression of lgt1 in the cytosol of S. cerevisiae resulted in severe toxic effects.…”
Section: Discussionsupporting
confidence: 78%
“…Using a reticulocyte-based translation system, we recently showed that Lgt1 effectively blocks mammalian protein synthesis in vitro (12,13). Similar results were obtained, when translation extracts from S. cerevisiae were programmed with mRNA coding for firefly luciferase.…”
Section: Toxicity Of Lgt1 In Wild Type S Cerevisiae Background-firstsupporting
confidence: 66%
See 3 more Smart Citations